2022
DOI: 10.1145/3516431.3516438
|View full text |Cite
|
Sign up to set email alerts
|

How Inclusive are We?

Abstract: ACM SIGMOD, VLDB and other database organizations have committed to fostering an inclusive and diverse community, as do many other scientific organizations. Recently, different measures have been taken to advance these goals, especially for underrepresented groups. One possible measure is double-blind reviewing, which aims to hide gender, ethnicity, and other properties of the authors. We report the preliminary results of a gender diversity analysis of publications of the database community across se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…However, they concluded none of these factors influenced significantly the gender ratio. Similarly, Bonifati et al (2022) did not find an effect on double-blind review over singleblind review even if they had data where the same conference had made the change in their review process. Both works (being from 2022) however concluded, that there is a chance that some of the effects are only visible after the next decade or so, when the current Ph.D. students become leaders of their own labs, for example.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…However, they concluded none of these factors influenced significantly the gender ratio. Similarly, Bonifati et al (2022) did not find an effect on double-blind review over singleblind review even if they had data where the same conference had made the change in their review process. Both works (being from 2022) however concluded, that there is a chance that some of the effects are only visible after the next decade or so, when the current Ph.D. students become leaders of their own labs, for example.…”
Section: Discussionmentioning
confidence: 95%
“…This number alone bases it in the high end of the reported 10-44% of computer science conferences in Cohoon et al (2011). In comparison to newer studies, average in computer systems was reported to be only around 10% in Frachtenberg and Kaner (2022) and 30-70% in database research reported in late 2021 (Bonifati et al, 2022). The distribution of the number of the PerCom articles over the years is illustrated in Figure 1.…”
Section: Gender In Accepted Articlesmentioning
confidence: 88%
See 3 more Smart Citations